Intergenerational struggles and technological dramas of the neobakala music scene - Leste,Eduardo (2021)
Abstract In late modernity, Western societies undergo profound processes of change that lead to tensions between different social actors, which sometimes occur in intergenerational terms. This article explores these tensions in the field of music through the neobakala scene, which is composed of adults who have created a nostalgic discourse to establish a hierarchy with other musical scenes created by youngsters. The concepts of nostalgia and generation, therefore, will be key in articulating this text but both will be critically approximated, since the two assume a presence of memory in their constitution (that is not always backed by evidence). In this sense, this article, which also explores the past of the neobakala scene, claims memory as a field on its own, differentiated from nostalgia and as a source of criticism of it. On the other hand, in the analysis of this nostalgia, the neobakala scene and the same intergenerational struggles that occur in this late modernity, this article will pay special attention to the role of technological changes. To this end, the article will resort to the concept of remediation and, above all, that of "technological drama", which will allow us to observe a process of reintegration in which the neobakala subversive past ends up aligning itself with power in a context of expansion of digital technologies.